Hubungan Kelengkapan Resume Medis terhadap Ketepatan Waktu Klaim BPJS Kesehatan di Puskesmas Klumbayan Barat Kabupaten Tanggamus - Eka Reni Sugianto; Febria Listina; Nurul Aziza (Malahayati Nursing Journal, 2025)
ABSTRACT Often Puskesmas usually cannot submit JKN claims on time, which will have an impact on the financial cycle of the Puskesmas and also affect health services to patients. The cause that is often encountered is the return of claim files because the diagnosis on the medical resume sheet submitted is incomplete or inaccurate. The data obtained from BPJS health Tanggamus Regency with a time span of submitting claims from January to April 2024 is 87.8% of the number of claims that are eligible to be paid from the total number of claims submitted by the First Level Health Facility. The purpose of this study was to determine the relationship between the completeness of medical resumes and the timeliness of BPJS health claims at the West Klumbayan Health Center, Tanggamus Regency. This type of quantitative research with a cross sectional approach. The population in this study were all BPJS health patients registered at the West Klumbayan Health Center as many as 428 patients, with a sample of 207 BPJS patients using purposive sampling technique. The research was conducted at the West Klumbayan Health Center, Tanggamus Regency in July 2024. Data collection using questionnaires and observation. Data analysis was univariate and bivariate (chi square). Univariate research results obtained as many as 144 (69.6%) respondents with complete medical resume completeness and as many as 163 (78.7%) respondents with appropriate claim timeliness. Bivariate analysis there is a relationship between the completeness of medical resumes and the timeliness of BPJS health claims at the West Klumbayan Health Center, Tanggamus Regency (p-value = 0.009). Suggestions for health workers must understand and apply the SOP for filling out medical resumes in accordance with applicable regulations and conduct periodic evaluations to improve the discipline of health workers with quality medical resume content. Keywords: Completeness of Medical Resumes and Timeliness of BPJS Claims  ABSTRAK Seringkali Puskesmas biasanya tidak bisa mengajukan klaim JKN tepat waktu akan berdampak pada siklus keuangan Puskesmas dan juga berpengaruh terhadap pelayanan kesehatan terhadap pasien. Penyebab yang sering dijumpai adalah adanya pengembalian berkas klaim karena diagnosa pada lembar resume medis yang diserahkan tidak lengkap atau tidak akurat. Adapun data yang diperoleh dari BPJS kesehatan Kabupaten Tanggamus dengan rentang waktu pengajuan klaim bulan Januari hingga April 2024 adalah sebanyak 87,8% jumlah klaim yang layak dibayarkan dari total seluruh pengajuan klaim yang diajukan oleh Fasilitas Kesehatan Tingkat Pertama. Diketahui hubungan kelengkapan resume medis terhadap ketepatan waktu klaim BPJS kesehatan di Puskesmas Klumbayan Barat Kabupaten Tanggamus. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh pasien BPJS kesehatan yang tercatat di Puskesmas Klumbayan Barat sebanyak 428 pasien, dengan sampel yang digunakan sebanyak 207 pasien BPJS menggunakan Teknik purposive sampling. Penelitian telah dilakukan di Puskesmas Klumbayan Barat Kabupaten Tanggamus pada bulan Juli 2024. Pengumpulan data menggunakan kuesioner dan observasi. Analisis data secara univariat dan bivariat (chi square). Univariat didapatkan sebanyak 144 (69.6%) responden dengan kelengkapan resume medis lengkap dan sebanyak 163 (78.7%) responden dengan ketepatan waktu klaim tepat. Analisis bivariat ada hubungan kelengkapan resume medis terhadap ketepatan waktu klaim BPJS kesehatan di Puskesmas Klumbayan Barat Kabupaten Tanggamus (p-value = 0.009). Saran bagi tenaga kesehatan wajib memahami dan menerapkan SOP pengisian resume medis sesuai dengan peraturan yang berlaku dan melakukan evaluasi berkala demi meningkatkan kedisplinan tenaga kesehatan dengan isi resume medis yang berkualitas Kata Kunci: Kelengkapan Resume Medis Dan Ketepatan Waktu Klaim BPJS